Assessment of knowledge and utilization of contraceptive methods among puerperal women at Saint-Nicolas Hospital in Haiti - Sarhns Lori Desruisseaux; Anne Beverly Blanchard; Calèbe Delva; Rose Evelyne Pierre; Vasthie Bernardin; Hendrick Etienne; Chamberly Huguens Ulysnor; Michael Jean Baptiste; Jonathan Leosthene; Waquinn Saint Loth; Benjamine Urimmaculus Scaïde (Journal of Global Health Economics and Policy)
# Background This study aimed to determine the level of knowledge of postpartum patients on traditional (lactation amenorrhea method (LAM), withdrawal, calendar) and modern (condoms, intrauterine devices (IUDs), pills, implants, sterilization) contraception methods available in Haiti as well as their behaviour towards them. We also sought to investigate possible correlations between the level of knowledge and other variables such as age, parity and level of education.